Influence of Current Ratio (CR), Return on Equities (RoE) and Price Earning Ratio (PER) on Share Prices: Study of Companies in Various Industrial Sectors Listed on the Stock Exchange Indonesian Effects 2018-2021 - Ade Maharini Adiandari; Ni Komang Ayu Astuti (GoAcademica Research & Publishing, 2023)
The aim of this research is to collectively explore the effects of the current ratio, return on equity, and price-earnings ratio on the stock prices of companies spanning various industries listed on the Indonesia Stock Exchange during the period from 2018 to 2021. This study involved a selection of 35 companies as samples, chosen through the purposive sampling method. The data employed in this research is of a secondary and quantitative nature. Data collection methods encompassed both observation and the analysis of documentary studies. The analytical approach used is multiple linear regression analysis. The findings indicate that, on the whole, the current ratio, return on equity, and price-earnings ratio exert a notable influence on stock prices. However, upon closer examination, it is evident that return on equity and price-earnings ratio individually demonstrate a favorable and substantial impact on stock prices.